Modulação autonômica da frequência cardíaca e sua relação com os fatores de risco e o polimorfismo do gene da ECA de pacientes com doença arterial coronariana - Kunz, Vandeni Clarice (2012)
The multifactorial nature of coronary artery disease (CAD) includes complications related to angina and acute myocardial infarction (AMI) and disorders involving sympathetic and parasympathetic cardiac autonomic modulation. The objective of this study was to evaluate the autonomic modulation of heart rate (HR) by linear and non-linear methods in healthy men and in patients with AMI and different percentages of coronary stenosis, as well as its relation with CAD risk factors. In order to evaluate heart rate variability (HRV), the HR and the RR intervals were recorded for 15 min in the supine position. Based on the results of this study, three manuscripts were written: The first manuscript presents the results of 10 men with AMI (57±9 years old) (2nd and 7th day after coronary event) and 11 healthy men (53±4 years old). The HRV analysis was carried out using linear methods in the time domain (TD=RMSSD and SDNN) and frequency domain (FD= low frequency (LF) and high frequency (HF) in normalized units (nu) and LF/HF) and using the non-linear methods approximate entropy (ApEn). A significant relationship between the linear and non-linear methods and the RMSSD, SDNN, LFun, HFun and LF/HF and ApEn indexes was observed. The linear and non-linear HRV indexes from the healthy group were higher than those of the AMI group on the 2nd and 7th days, which suggests that the analysis of HRV with linear methods in the TD and FD and the use of ApEn for linear analysis are in agreement, both for healthy subjects and patients after AMI. The second manuscript presents the results of 52 men (54±5 years old) divided into two groups with coronary obstruction CAD+ ≥ 50% (n=18) and CAD- < 50% (n=17) and one control group (n=17). HRV analysis was carried out with Shannon entropy (SE) and symbolic analysis (0V and 2ULV). The patients with DAC+ presented lower SE (complexity), 2ULV (vagal predominance) and higher 0V (sympathetic predominance) than the DAC- and control groups, which indicates that cardiac autonomic disorder is related to the degree of coronary occlusion and to cardiac impairment. The third manuscript presents the results for risk factors, ACE I/D polymorphism and the indexes in the TD and FD of 151 patients with CAD (56±8 years old, DD=54, DI=70 and II=27). The results show that there was no relation between the ACE I/D polymorphism and HR, BP or HRV. However, the highest indexes of the HRV, which reflect vagal autonomic modulation, are related to a lower percentage of stenosis and the use of ACE inhibitors.